Assessing degradation of abandoned farmlands for conservation of the monte desert biome in Argentina - Yanelli, Florencia A. (2014)
Land abandonment is a major issue worldwide. In Argentina, the Monte Desert is the most arid rangeland, where the traditional conservation practices are based on successional management of areas excluded to disturbances or abandoned. Some areas subjected to this kind of management may be too degraded, and thus require active restoration. Therefore, the aim of this study was to assess whether passive succession-based management is a suitable approach by evaluating the status of land degradation in a protected area after 17–41 years of farming abandonment. Soil traits and plant growth forms were quantified and compared between sites according to time since abandonment and former land use (cultivation and grazing). Two variables were calculated using the CORINE-CEC method, i.e., potential (PSER) and actual (ASER) soil erosion risk. PSER indicates the erosion risk when no vegetation is present, while ASER includes the protective role of vegetation cover. Results showed that land use history had no significant effect on plant growth forms or soil traits (p > 0.05). After more than 25 years since abandonment of farming activities, soil conditions and vegetation cover had improved, thus having a lower ASER. Nevertheless, the present soil physical crusts may have delayed the full development of vegetation, enhancing erosion processes. Overall, this study indicates that succession-based management may not be the best practice in terms of conservation. Therefore, any effort for conservation in the Monte Desert should contemplate the current status of land degradation and potential vegetation recovery.